Battery Demonstration Unit - Science History Institute (2023)
A battery demonstration unit constructed by Alan MacDiarmid (1927-2007), winner of the 2000 Nobel Prize in Chemistry for "the discovery and development of conductive polymers." MacDiarmid, Hideki Shirakawa (1936-), and Alan Heeger (1936-) shared the prize for their discovery that plastics could be made to be electrically conductive. Conductive polymers exhibit the electronic and magnetic properties of metals but retain the mechanical properties of organic polymers. Prototype cells such as this were built to test the electro-conductivity properties of polymers.
Keywords: MacDiarmid, Alan G., 1927-2007; Electric batteries; Conducting polymers; Electricity--Study and teaching; Nobel Prize winners; Organic conductors; Lithium ion batteries